Distribution of Drought on Agricultural Land in Palabuhanratu District Sukabumi Regency - Ayu Handayani; Hafid Setiadi (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2023)
Drought is one of the natural disasters that causes substantial losses to food crop production, water supply in several important sectors such as industry, settlements, and agriculture. Climate change often causes drought on agricultural land and can indirectly threaten livelihoods and food security. This study aims to analyze the distribution of drought on agricultural land and examine the relationship between physical conditions. Drought monitoring study using remote sensing methods on Landsat 8 OLI imagery with the Normalized Difference Drought Index (NDDI) algorithm is the result of combining two parameters, namely the Normalized Difference Vegetation Index (NDVI) and Normalized Difference Water Index (NDWI). The results of the study show the distribution of agricultural land drought in Palabuhanratu District, Sukabumi Regency during 2018-2021 with five classes (normal, mild, moderate, severe, and very severe), and a very severe drought category of 80.78 ha in 2021, followed by 2018 an area of 32.09 ha. The most potential drought areas are in Palabuhanratu District, namely Jayanti Village and Citepus Village.